Virtual Public Space in Sketching Community - Stefy Prasasti Anggraini; Ahmad Rosyid Wahyu Anggoro (Departement of Architecture, Universitas Islam Indonesia, 2021)
Virtual Public Space in the sketch community has created by physical distancing during the covid-19 pandemic. The development of the spread of Covid-19, which is experiencing an increase, has changed the physical public space to turn into a virtual public space. Therefore the public space becomes part of the social space for a community, one of which is the sketch community. The sketch community in urban sketchers began to switch to using virtual public space during a pandemic. This study aims to find a pattern from virtual public space in a sketching community that architecture students follow. The method used is the descriptive qualitative method by taking four case studies from communities in Indonesia. According to students, the placemaking pattern of virtual public space from these four communities is necessary and valuable for independent sketching learning.Keywords: community; placemaking; sketching; virtual public space